2014
DOI: 10.1007/s00424-014-1455-9
|View full text |Cite
|
Sign up to set email alerts
|

Myofilament dysfunction as an emerging mechanism of volume overload heart failure

Abstract: Two main hemodynamic overload mechanisms [i.e., volume and pressure overload (VO and PO, respectively] result in heart failure (HF), and these two mechanisms have divergent pathologic alterations and different pathophysiological mechanisms. Extensive evidence from animal models and human studies of PO demonstrate a clear association with alterations in Ca(2+) homeostasis. By contrast, emerging evidence from animal models and patients with regurgitant valve disease and dilated cardiomyopathy point toward a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
5
0
1
Order By: Relevance
“…In pressure-overload activation of the Akt/mTOR signaling cascade is enhanced with hyperglycemia (Hernandez et al, 2013), but this pathway was not found to be upregulated in highfructose aortic regurgitation (Bouchard-Thomassin et al, 2011). However, aortic-regurgitation does not produce pure volumeoverload (Wilson and Lucchesi, 2014), and others have reported that activation of Akt/mTORC1 pathway has a central role in promoting eccentric hypertrophy in aorto-caval shunts with the level of pathway activation being a function of LV end-diastolic stress (Ikeda et al, 2015) (Figure 4).…”
Section: Metabolic Remodelingmentioning
confidence: 98%
See 2 more Smart Citations
“…In pressure-overload activation of the Akt/mTOR signaling cascade is enhanced with hyperglycemia (Hernandez et al, 2013), but this pathway was not found to be upregulated in highfructose aortic regurgitation (Bouchard-Thomassin et al, 2011). However, aortic-regurgitation does not produce pure volumeoverload (Wilson and Lucchesi, 2014), and others have reported that activation of Akt/mTORC1 pathway has a central role in promoting eccentric hypertrophy in aorto-caval shunts with the level of pathway activation being a function of LV end-diastolic stress (Ikeda et al, 2015) (Figure 4).…”
Section: Metabolic Remodelingmentioning
confidence: 98%
“…The extracellular matrix (ECM) regulates contractile performance via direct manipulation of myocardial stiffness as well as by coordinating myocardial remodeling (Baharvand et al, 2005). In volume-overload, ECM is degraded with reductions in collagen fractional volume, and increases in elastin (Ryan et al, 2007;Wilson and Lucchesi, 2014;Hutchinson et al, 2015). Collagen reductions occur due to increased matrix metalloproteinases (MMPs) activity and a concurrent decrease in their inhibitors, tissue inhibitors of MMPs (TIMPs) (Levick et al, 2008;Wilson and Lucchesi, 2014).…”
Section: Mechanical Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…A central feature of heart failure (HF) is contractile dysfunction (either systolic or diastolic) accompanied by ventricular wall remodelling (Hamdani et al . ; van der Velden, ; Wilson & Lucchesi, ) and impaired β‐adrenergic signalling that disrupts downstream protein phosphorylation (Post et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A seguir, a cabeça da miosina de cadeia pesada (MCP) liga-se ao ATP e ao sofrer hidrólise (ADP+Pi), a miosina adquire grande afinidade pela actina, deslizando pelo filamento fino, o que causa a contração do miocárdio. Após a liberação do Pi, um novo ciclo de pontes cruzadas é formado (Boron;Boulpaep, 2008;Wilson;Lucchesi, 2014).…”
Section: Introductionunclassified